The relationships between perfectionism, mindfulness and academic burnout with mediating role of unconditional self-acceptance and coping style in in high school boy students in Tehran - mostafa jalalvand; farh lotfikashani; shahram vaziri (مجله علوم روانشناختی, 2020)
Background: Previous studies have determined that academic burnout is influenced by a variety of variables including perfectionism and mindfullness, but the important point in these studies is that the process of influencing has not been shown, especially through the mediating variabl. Aims: The aim of the present study was to examine the model of causal relationship of perfectionism and mindfillness with academic burnout with mediating role of unconditional self-aceptance and coping styles. Method: The population of this study consists of all all male high school students in Tehran in 1395-96. The sample of this study consists of 510 students who were selected by multi-stage random sampling method. The variables were measured by Multidimensional Perfectionism Scale Frost et al (1990) and Maslach burnout Questionnair (2002), Coping Inventory for Stressful Situations Endler and Parker (1990) and The Kentucky Inventory of Mindfulness Skills Baer et al (2004). Results: The Data were analyzed according to structural equation modeling (SEM) method. The fitness indicators of the model showed the proper fit with the data (χ2=2/969, GFI=0/933, AGFI=0/901, CFI=0/975, NFI=0/963, RMSEA=0/063). The result showed that the direct paths of adaptive perfectionism to academic burnout, unconditional self-aceptance, problem-oriented coping and problem-oriented coping were statistically significant (p<0/05). Also, the paths from maladaptive perfectionism to unconditional self-aceptance, problem-oriented coping and emotion-oriented coping were statistically significant (p<0/05). The relationship between mindfulness and unconditional self-aceptance was significant (p<0/05).The relationship between maladaptive prfectionism and academic burnout was not significant (p>0/05). In addition, the relationship between mindfulness and academic burnout, problem-oriented coping, and emotion-oriented coping styles was not insignificant (p>0/05). The results of indirect path from adaptive perfectionism and maladaptive perfectionism and mindfullness to academic burnout by unconditional self-aceptance, problem-oriented coping and emotion-oriented coping were significant. Conclusions: The results of the research showed that the perfectionism and mindfulness are directly and indirectly related to academic burnout whit the mediators of coping styles and unconditional self-aceptance.